Mortality of Community-Acquired Pneumonia in Korea: Assessed with the Pneumonia Severity Index and the CURB-65 Score - Kim, Hye In; Kim, Shin Woo; Chang, Hyun Ha; Cha, Seung Ick; Lee, Jae Hee; Ki, Hyun Kyun; Cheong, Hae Suk; Yoo, Kwang Ha; Ryu, Seong Yeol; Kwon, Ki Tae; Lee, Byung Kee; Choo, Eun Ju; et al. (Journal of Korean medical science, 2013)
The pneumonia severity index (PSI) and CURB-65 are widely used tools for the prediction of community-acquired pneumonia (CAP). This study was conducted to evaluate validation of severity scoring system including the PSI and CURB-65 scores of Korean CAP patients. In the prospective CAP cohort (participated in by 14 hospitals in Korea from January 2009 to September 2011), 883 patients aged over 18 yr were studied. The 30-day mortalities of all patients were calculated with their PSI index classes and CURB scores. The overall mortality rate was 4.5% (40/883). The mortality rates per CURB-65 score were as follows: score 0, 2.3% (6/260); score 1, 4.0% (12/300); score 2, 6.0% (13/216); score 3, 5.7% (5/88); score 4, 23.5% (4/17); and score 5, 0% (0/2). Mortality rate with PSI risk class were as follows: I, 2.3% (4/174); II, 2.7% (5/182); III, 2.3% (5/213); IV, 4.5% (11/245); and V, 21.7% (15/69). The subgroup mortality rate of Korean CAP patients varies based on the severity scores and CURB-65 is more valid for the lower scores, and PSI, for the higher scores. Thus, these variations must be considered when using PSI and CURB-65 for CAP in Korean patients.